Myth, symbol, and culture - Geertz, Clifford; Fernandez, James W.; Douglas, Mary; Manuel, Frank E.; Manuel, Fritzie P.; Shklar, Judith N.; Brower, Reuben A.; Marcus, Steven; Adams, Robert M. (W. W. Norton & Company, Inc., 1971)
Exploring the meaning of metaphors, nine scholars have contributed essays to this volume, ranging in subject from a Balinese cockfight through literary criticism to a home-cooked meal. The symbols men have used and continue to use are considered from the viewpoint of anthropology, history, government, and literature. This collection of interdisciplinary studies of meaning will be of particular interest to students of anthropology and literature.